2007
DOI: 10.1001/archinte.167.12.1233
|View full text |Cite|
|
Sign up to set email alerts
|

Disparities in Health Care Are Driven by Where Minority Patients Seek Care

Abstract: Background: Racial/ethnic disparities in health care are well documented, but less is known about whether disparities occur within or between hospitals for specific inpatient processes of care. We assessed racial/ethnic disparities using the Hospital Quality Alliance Inpatient Quality of Care Indicators. Methods: We performed an observational study using patient-level data for acute myocardial infarction (5 care measures), congestive heart failure (2 measures), community-acquired pneumonia (2 measures), and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
247
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 306 publications
(269 citation statements)
references
References 20 publications
19
247
3
Order By: Relevance
“…While our findings are consistent with a large body of literature documenting the association of poorer health outcomes with increasing percent of local residents who are Black, and with racial segregation, [47][48][49][50][51][52][53][54][55][56] they run counter to findings from the emerging literature that focuses exclusively on these exposures' relationship to breast cancer mortality. Haas et al 15 found no relationship between racial segregation (operationalized as isolation) and breast cancer mortality, and Warner and Gomez 16 found an inverse relationship between Black neighborhood racial composition and breast cancer mortality among Black women and a positive relationship for White women, controlling for metropolitan segregation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While our findings are consistent with a large body of literature documenting the association of poorer health outcomes with increasing percent of local residents who are Black, and with racial segregation, [47][48][49][50][51][52][53][54][55][56] they run counter to findings from the emerging literature that focuses exclusively on these exposures' relationship to breast cancer mortality. Haas et al 15 found no relationship between racial segregation (operationalized as isolation) and breast cancer mortality, and Warner and Gomez 16 found an inverse relationship between Black neighborhood racial composition and breast cancer mortality among Black women and a positive relationship for White women, controlling for metropolitan segregation.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies found evidence that racial minorities are more likely to receive care from lower quality facilities than their White counterparts. [52][53][54]62 For example, hospital and physician "volume" is thought to be connected to quality of care. 55 In a recent study where there was an established association between volume and mortality, Black patients in New York City were at a double disadvantage because they were less likely than their White counterparts to use high-volume hospitals and surgeons for breast cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that variations between health facilities contribute to treatment disparities in other countries, 18,[34][35][36][37][38][39] particularly the United States, where ethnic segregation of healthcare is marked 36,40 and is likely to be a major cause of treatment differences between black and white patients. 35,37,41,42 We made some attempt to assess the influence of facility differences on Maori/non-Maori treatment disparities by adjusting for the type of hospital where patients underwent surgery (treating this as the patient's primary treatment facility).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers should consider recruiting participants from settings such as county health departments and hospital emergency rooms [23]. Future studies should also examine how diabetes-related distress, self-efficacy, and coping methods may vary depending on life-stage (e.g.…”
Section: Strengths and Limitationsmentioning
confidence: 99%